Pemanfaatan Aplikasi Tiktok Sebagai Personal Branding Di Instagram (Studi Deskriptif Kualitatif Pada Akun @bowo_allpennliebe) - Susilowati Susilowati (Jurnal Komunikasi, 2018)
One of Instagram's presence is that it has other functions, besides being able to build a brand, Instagram can also build personal branding of its owners. Similarly, Bowo Alpenliebe uses Instagram to form his personal branding by making videos using the Tik Tok application. The purpose of the research is to find out the use of Tik Tok as a personal branding on Instagram. Research uses qualitative methods with a descriptive approach. The results of Bowo Allpenliebe's research have formed 8 personal branding concepts, namely; Specialize in uploading videos on their Instagram accounts (Ability, Lifestyle, Mission, Product and Profession). Personality, Bowo is a creative boy. Difference, the account contains videos of his creation using the Tik Tok application. Seen, in uploading the Tik Tok video, always try with a variety of songs and movements, and do it continuously and always filled with positive and negative comments. Unity, Bowo has many fans and haters. Firmness, Bowo has followed the times to form his personal branding by creating and uploading Tik Tok videos through his Instagram account. Good name, Bowo has tried to establish his good name through his Instagram account. Bowo Allpenliebe has also formed a personal branding using 4 features of 9 features in Instagram, namely; Unique and Interesting Cover Image Options, By (using) Audio, using Narration For Video Branding and also using the appropriate Hashtag, due to the creation of Video using the features provided in the Tik Tok application.